DESIGN OF AN AI-POWERED PREDICTIVE MAINTENANCE SYSTEM FOR INDUSTRIAL IOT NETWORKS - Dhiraj Kelly Sawlani; Sukril Rahman Zega; M. Ridho (Adisam Publisher, 2025)
The Industrial Revolution 4.0 presents new challenges in industrial asset management, particularly regarding equipment maintenance. Traditional maintenance approaches, both reactive and preventive, have proven to be less efficient because they cause downtime and waste costs. Therefore, predictive maintenance emerges as a promising solution through the utilization of the Internet of Things (IoT) for real-time data collection and Artificial Intelligence (AI) for failure pattern analysis. This article presents a literature review on the design of an AI-based predictive maintenance system integrated with an industrial IoT network. The study was conducted by searching literature from reputable databases such as IEEE Xplore, ScienceDirect, ACM, and Springer, using the keywords